Ibn Hisham's (d. 577 AH) approach to strictness and his support for classical and colloquial Arabic in his book (Introduction to Correcting the Tongue) (Journal of the College of Basic Education, 2025)
The research (Ibn Hisham's (d. 577) approach to his support for classical and colloquial Arabic in his book Introduction to Correcting the Tongue) aims to reveal Ibn Hisham's method in dealing with speech in which common people have made mistakes. This research opens a horizon for rooting the speech of the common people of our time according to those corrections, and the method followed by Ibn Hisham in his book.The importance of the research lies in its clarification of the correct path in preserving the language from mistakes, by clarifying Ibn Hisham's approach in proving linguistic correctness.The research was divided into two sections, preceded by an introduction, to clarify the research plan. The first section was titled (The Concept of Grammar and the Reasons for Its Occurrence), in which I presented the meaning of grammar, the reasons leading to its occurrence in the language, and the most important books that have been written by the public. The second section is titled (Ibn Hisham’s Methodology in Grammar), and it represents the applied aspect of the study. I analyzed Ibn Hisham’s responses, thereby revealing his approach to grammar in people’s speech, and Al-Zubaidi (d. 379 AH), and Ibn Makki Al-Siqilli (d. 510 AH). I reached a number of results, the most important of which is that criticizing people’s speech must be based on evidence that proves the validity of Ibn Hisham’s speech, in addition to the need for broad knowledge in order to confront criticizing scholars such as Al-Zubaidi and Ibn Makki Al-Siqilli